The effect of warm compresses on perineal tear and pain intensity during the second stage of labor: A randomized controlled trial - Soumaya Modoor; Howieda Fouly; Hawazen Rawas (Belitung Raya Foundation, Indonesia, 2021)
Background: Warm compress is believed to reduce perineal tear occurrence and decrease pain intensity during the second stage of childbirth.Objective: This study aimed to determine the effect of warm compresses on perineal tear and pain intensity during the second stage of labor. Methods: A randomized controlled trial was conducted between 28 September 2018 to 30 October 2018 in King Khaled Hospital (KKH), affiliated with the Ministry of National Guard Hospital Affairs, King Abdul-Aziz Medical City Western Region, Saudi Arabia. According to eligibility criteria, the sample randomly recruited through lottery included 100 primigravida pregnant women, with 50 in each intervention and control group. Data were presented in the form of frequency and percentages, standard deviation, and mean. Chi-square test was used for data analysis, with p-value significance at ˂ 0.05.Results: Sociodemographic data revealed no statistically significant difference in the age, education, occupation, and residence of both the control and experimental group. The perineum area’s pain intensity after birth showed a statistically significant difference between the intervention and the control groups (p = 0.001). The perineal tear was also significantly different between both groups (p = 0.001). Conclusion: The applied warm compresses on the perineum area positively reduce second and third-degree perineal tear and pain intensity during the second stage of labor and after childbirth. Therefore, midwives and nurses are expected to actively provide effective planned in-service training programs regarding warm compresses' advantages in the second stage of labor and apply this procedure actively.